PENDAMPINGAN PENGOLAHAN CHIPS (KERIPIK) PISANG TONGKA LANGIT KEPADA MASYARAKAT PETANI DI NEGERI LILIBOOI KECAMATAN LEIHITU BARAT - Breemer, Rachel; Palijama, Syane; Pattiruhu, Gysberth (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2025)
This Community Service (PkM) program was conducted to address the limited knowledge of the residents of Lilibooi Village, Leihitu Barat District, regarding the potential of Pisang Tongka Langit (Musa troglodytarum L.) as an abundant local commodity. Currently, this banana is generally sold in fresh form, making it highly perishable and underutilized as a value-added product. Situation analysis revealed that the community lacks understanding of how to process this natural resource into beneficial products, despite its high content of provitamin A and total carotenoids, which make it suitable as a functional food. The proposed solution involved organizing an educational workshop and hands-on training on processing Pisang Tongka Langit into high-quality banana chips . The method included lectures on nutritional potential and processing techniques, followed by demonstration and direct practice. This activity aimed to promote food diversification and create business opportunities to improve local economic welfare. The results indicated a positive community response, increased awareness of the banana’s potential, and improved skills in producing crispy, shelf-stable chips . However, challenges such as limited processing equipment and raw material availability require further support. In conclusion, the training provided valuable knowledge and practical skills as an entrepreneurial foundation for the residents of Lilibooi Village.